Pengaruh Substitusi Tepung Beras Hitam (Oryza Sativa L. Indica) Pada Pembuatan Roti Tawar Terhadap Daya Terima Konsumen - Dwi Meliana Putri; Guspri Devi Artanti; Sachriani (Jurnal Sains Boga, 2021)
The objective of this study was to learn the effect of black rice flour substitution on white bread processing to consumer acceptance, covering aspects of external (volume and skin color), and aspects of internal (skin character, crumb color, flavor, taste and texture). This study used an experimental method performed at the Laboratory of Pastry and Bakery, Food and Nutrition Program, Faculty of Technology, State University of Jakarta from January until December 2020. Organolaptic test conducted on 25 no trained panelists. The results of the descriptive data showed that white bread substitute black rice flour as much as 10% are most preferred by consumers in all aspects, with an average of 4.52 aspects of volume; outer aspect of color 4.24; aspects of the crumb of 4.16; aspects of the crumb color of 4.12; aroma aspects of 4.32; flavor aspects of 4.4; and crumb texture aspects of 4.48 which all aspects a showed that are in the range of categories like to very like. Hypothesis analyze using Friedman test showed that there is a substitution effect of black rice flour on white bread processing in percentage 10%, 20%, and 30% on consumer acceptance on all aspects: volume, the color of the skin or crust, crumb / pores, crumb color, flavor, taste, and texture. Tuckeys test results showed that white bread substitute black rice flour in percentage 10% dan 20% are the preferred consumer, with the recommended substitution formula as much as 20% as the best usage of the black rice.